2022
DOI: 10.1111/are.16060
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein and astaxanthin levels on growth performance, hepatopancreas antioxidant capacity and immunity of giant freshwater prawn ( Macrobrachium rosenbergii )

Abstract: The giant freshwater prawn, Macrobrachium rosenbergii, is abundantly farmed in East China and Southeast Asia. To date, limited information exists on the relationship between protein and astaxanthin, and the antioxidation and non‐specific immunity functions. This study was conducted to investigate the effects of dietary protein and astaxanthin levels on growth, hepatopancreas antioxidant capacity and non‐specific immune response of prawns. Further, the interaction between protein and astaxanthin was determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Excessive astaxanthin had the negative effects on the above gene expression. Similar results appeared at giant freshwater prawn (Macrobrachium rosenbergii), which indicated that excessive astaxanthin may have adverse effects on several enzymes involved in the immune system [49]. However, studies in whiteleg shrimp by Yu et al…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Excessive astaxanthin had the negative effects on the above gene expression. Similar results appeared at giant freshwater prawn (Macrobrachium rosenbergii), which indicated that excessive astaxanthin may have adverse effects on several enzymes involved in the immune system [49]. However, studies in whiteleg shrimp by Yu et al…”
Section: Discussionmentioning
confidence: 72%
“…Among them, astaxanthin is proved to be the most predominant pigment in shrimp [7]. In addition to improve body color, astaxanthin also promotes shrimp health through enhancing the immune response [8] and relieving oxidative stress [9]. Astaxanthin is the strongest natural antioxidant to date and activates the Keap1-Nrf2 system to scavenge free radical produced from external stress [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the addition of an appropriate amount of astaxanthin to the feed can significantly promote the growth of both P . vannamei and Penaeus japonicus [ 36 , 37 ]. In this study, it was observed that the average mass and the rate of weight gain of P .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that adding astaxanthin to the feed can significantly improve the growth performance and low-oxygen tolerance of P. vannamei [35]. Furthermore, the addition of an appropriate amount of astaxanthin to the feed can significantly promote the growth of both P. vannamei and Penaeus japonicus [36,37]. In this study, it was observed that the average mass and the rate of weight gain of P. vannamei fed with both MCs and astaxanthin were higher compared to the MC group.…”
Section: Discussionmentioning
confidence: 99%